Performance of anti‐Müllerian hormone (AMH) levels measured by Beckman Coulter Access AMH assay to predict oocyte yield following controlled ovarian stimulation for in vitro fertilization. (8th April 2019) - Asada, Yoshimasa; Tsuiki, Miyako; Sonohara, Megumi; Fukunaga, Noritaka; Hattori, Yukio; Inoue, Daichi; Ito, Rie; Hashiba, Yoshiki
Abstract: Purpose: We evaluated the performance of anti‐Müllerian hormone (AMH) measured by the Beckman Coulter fully automated Access assay to predict oocyte yield following controlled ovarian stimulation (COS) for in vitro fertilization (IVF). Methods: The correlation between the Access assay and the pre‐mixing method with Generation II ELISA assay (Gen II pre‐mix assay) was assessed using 230 blood samples. The relationship of AMH level measured by the Access assay and the actual number of oocytes retrieved following COS was assessed using 3296 IVF cycles. The performances of AMH, follicle stimulating hormone (FSH), and estradiol (E2) in predicting the responses to COS were also evaluated by constructing receiver operating characteristic (ROC) curves. Results: The AMH levels measured just before oocyte retrieval by the Access assay and the number of oocytes retrieved following COS showed a good correlation with R = 0.655. The ROC analysis revealed that the sensitivity of AMH was comparable with or lower than that of E2 but higher than that of FSH. Conclusions: With the improved Access AMH assays, AMH was as sensitive as E2 and could become an accurate marker of ovarian response to COS in more than 3000 Japanese IVF patients.